Penggunaan Aplikasi Benime pada Pembelajaran Bahasa Arab Kelas VI SD IT Ar - Rahman Palangki - Adam Mudinillah; Amrina Amrina; Distya Leginta Vujiachi (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2022)
Language is a very basic thing for every human being, not only for communication but alsoas a forum for the prosecution of knowledge. At this time, other languages are urgentlyneeded because of the increasing circulation of information using other languages, as wellas Arabic itself. In the process of learning Arabic, there are several problems or difficultiesfaced at the IT Ar-Rahman Palangki Elementary School. With the development oftechnology at this time, therefore technology can be a solution to the difficulties broughtinto the teaching and learning process of Arabic at SD IT Ar-Rahman Palangki. This is dueto the technology that we can use to assist in making interesting learning media, especiallyapplications that can be accessed on Android in the form of images, sounds, and movinganimations, such as the Benime application. The benime app itself is an animated videomaker app for a more interesting percentage.